EVALUASI PENGELOLAAN KOPERASI DITINJAU DARI UNDANG-UNDANG NOMOR 25 TAHUN 1992 (STUDI KASUS PADA KOPERASI SERBA USAHA KUTA MIMBA DAN KOPERASI MURAH REJEKI, KABUPATEN BADUNG, BALI) - Astuti, Dwi Yuni; Pascarani, S.S, M.Si, Ni Nyoman Dewi; Wismayanti, S.E., M.AP, Kadek Wiwin Dwi (CITIZEN CHARTER, 2015)
ABSTRACT The Law of Cooperative No. 25 of 1992 had been trusted again by government after the Law No. 17 of 2012 was revoked because it didn’t compatible with the spirit of cooperatives. The cooperatives in Indonesian have been increased, however those only in quantity sides, not accompanied by the quality sides. One of the important factor to realizing the quality of cooperatives is manage them properly and professionally. This study used descriptive qualitative method. To get the data, researcher interviewed the informant directly and observed by herself the phenomenon in the field. The result of this research are that management of both cooperatives have been conducted in accordance with the applicable law. However, the management in Koperasi Murah Rejeki has not operating effectively and efficiently yet because due to lack of human resources to manage it. Whereas, the management in KSU Kuta Mimba has already performing well. Furthermore, the form of the government’s role in improving the quality of cooperatives through Department of Cooperatives, Small and Medium Enterprises, Industries, and Trades of Badung Regency are to foster cooperatives by way of education, training, and counseling, and then providing facilities, monitoring and evaluating the cooperatives at Badung Regency. Keywords: cooperative management, the Law of Cooperative No. 25 of 1992, regency government’s role